Mosque Jurisprudence-Based Moderation Da‘wah for Conflict Mitigation: a Case Study in Mojokerto Indonesia - Miftakhur Ridlo; Abdullah Khanif; Hadi Ismail (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study examines mosque-based religious moderation da‘wah grounded in fiqh al-masjid as a model for mitigating socio religious conflict at the grassroots level in Mojokerto Regency, Indonesia. Employing a qualitative case study approach, data were collected through in depth interviews, observations, and document analysis involving mosque administrators (takmir), religious leaders, officials of the Indonesian Mosque Council (DMI), and representatives of the Ministry of Religious Affairs. The findings reveal that religious moderation is operationalized through interconnected dimensions, including humanity (insaniyah), public benefit (maslahah), justice (‘adliyyah), balance (mubādalah), constitutional compliance (dusturiyah), national commitment (mu‘āhadah waṭaniyah), tolerance (tasāmuḥ), anti violence, and respect for local tradition (‘urfiyah). These dimensions are manifested in sermon narratives, participatory mosque governance, inclusive spatial arrangements, humanitarian and economic empowerment programs, and culturally sensitive practices. Analytically, the study demonstrates that moderation da‘wah becomes effective when ethical principles are institutionalized through clear policies, sermon guidelines, and conflict resolution mechanisms rather than remaining at the level of normative discourse. The study contributes theoretically by integrating religious moderation, mosque jurisprudence, and conflict studies into a coherent analytical framework, and practically by offering a model that can be adopted by mosque institutions and policymakers to strengthen social cohesion, prevent radicalism, and promote peaceful coexistence in plural societies.